2012
DOI: 10.1088/1742-2132/9/2/241
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Shear wave profiles from surface wave inversion: the impact of uncertainty on seismic site response analysis’

Abstract: We discuss a study on the effect of surface wave solution non-uniqueness on seismic site response. The inversion approach used in the considered paper may lead to a significant overestimation of the uncertainties due to solution non uniqueness. We also address the numerical simulation of seismic site response. We apply a consistent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
1
8
1
Order By: Relevance
“…The Discussers agree with the experimental uncertainty bound reported in our paper but they don't agree with the comparison of the bounds with an empirical formula proposed by Boaga et al [2]. Empirical formula given by Boaga et al [2] has been challenged by Socco et al [3]. Boaga et al [4] countered strongly what the Discussers called inconsistency at the lower frequencies.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The Discussers agree with the experimental uncertainty bound reported in our paper but they don't agree with the comparison of the bounds with an empirical formula proposed by Boaga et al [2]. Empirical formula given by Boaga et al [2] has been challenged by Socco et al [3]. Boaga et al [4] countered strongly what the Discussers called inconsistency at the lower frequencies.…”
Section: Discussioncontrasting
confidence: 62%
“…We had just have shown a comparison with our experimental uncertainty bound by using the proposed expression. The Discussers pointed out that the papers of Socco et al [3] and Pettiti et al [6] have not been cited in our paper. Socco et al [3] commented on Boaga et al [2] and the reply given by Boaga et al [4] appears to be quite logical.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They also refer to another study (Boaga et al, 2011) in which it was reported that, in the case of a gradual velocity increase with depth, solution non-uniqueness deeply affects the accuracy of seismic response analyses: for low impedance contrast the effect is much more pronounced than for high impedance contrast, for which the equivalent solutions have a very little influence. The latter was already discussed by Socco et al (2012), highlighting the importance of a correct procedure in ground response analysis: errors in the selection and application of input motions in seismic response simulation can indeed affect the obtained results.Roy et al claim that the inversion uncertainty has a pronounced effect on the 1D ground response analysis particularly for the far-field earthquake scenarios: this can mislead the calculations for design ground motions if these uncertainties are not properly addressed. …”
mentioning
confidence: 86%
“…They attribute this to surface wave depth resolution issues, non-uniqueness of the inversion procedures and/or the energy content of the signals used. The consequences of the uncertainties related to nonuniqueness of site responses have been a matter of discussion in recent years Foti et al 2009;Socco et al 2012;Boaga et al 2013;Jakka et al 2014;Comina and Foti 2015;Griffiths et al 2016;Cox and Teague 2016), with some authors claiming that the great uncertainty in Vs profiles leads to high variability of the site responses, although others do not agree. However, considering that the bedrock velocity is well known (e.g., through large arrays or other indirect information) and the velocity profiles are coherent with other indicators (e.g., the ambient vibration H/V frequency peak), the impact of nonuniqueness on site responses remains acceptable.…”
Section: Introductionmentioning
confidence: 99%